Highly efficient and reusable Ru-NaY catalyst for the base free oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic acid - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy (Catalysis Today, 2021)
Oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) is an important reaction for the production of recyclable bio-based polymers. Herein, we report a series of Ru nanoparticles supported on NaY zeolites catalysts for the oxidation of HMF to FDCA. The catalysts were prepared by simple ion exchanged method. Among all the catalysts, the optimized 3 wt % Ru-NaY catalyst showed superior catalytic activity under base free conditions with a shorter period of reaction time. The conversion of HMF was 100 % with 94 % FDCA yield. This catalyst was reused for fourth cycles, with an insignificant decrease in the yield of FDCA. H2-chemisorption and HRTEM studies confirmed that high metal dispersion and small size of Ru nanoparticles play vital roles for the HMF oxidation. In addition, the acidic hydroxyl groups of the supercage as well as higher amount of metallic Ru° are also responsible for the high yield and productivity of FDCA.